(untitled) - Derakhshani, Dariush (Indianapolis, IN, 2006)
3D animation and effects software is the first choice of film and video artists, game developers, and 3D design professionals. Discover how to build, render, and animate your own digital models and scenes, and begin to develop professional-level Maya skills with the latest edition of this popular bestseller. Starting with the basics, the book builds from the ground up, combining straightforward text with practical examples that make it fun and easy to learn Maya's core features while introducing new Maya 8 elements such as improved polygon tools and enhanced rendering with mental ray. Clear-cut, engaging lessons let you experiment using the wealth of files provided on the CD-ROM. You'll also find an abundance of instructional and inspirational Maya creations in the full-color insert. The accompanying CD-ROMs images, movies, and scene files let you view material from the book right on your own computer. Tackle all-new rendering and dynamics tutorials and much more.
Keywords: Maya ( Computer file ),Three-dimensional display systems,Computer graphics,Đồ họa máy tính,Maya (Chương trình máy tính),Hệ thống hiển thị ba chiều,Computer animation,Hoạt hình máy tính